The composition of matter : symposium honouring Johannes Geiss on the occasion of his 80th birthday - Steiger, R. von (Springer, 2017)
This volume consists of papers developed from a joint ACE/ISSI symposium on the "Composition of Matter" honoring the occasion of Johannes Geiss's 80th birthday The purpose of the symposium was to explore new insights into the composition of solar-system and galactic matter, and fractionation processes affecting samples of this matter, that have been brought about by recent space missions, ground-based studies, and theoretical advances. It was convened by G.M. Mason (chair), P. Bochsler, J.J. Connell, G. Gloeckler, M.H. Israel, R.A. Mewaldt, R. von Steiger, M.E. Wiedenbeck, and T.